… and All Men and Women Are Critics or Criticism in a MirageUniverse. - STEFANOVA, Kalina (Theatrical Colloquia, 2022)
This text/speech is an attempt to provoke discussion or at least thoughts regarding the increasing omnipresence of the false in our reality – something which results in sort of a theatricality in a negative connotation of the word. A theatricality that has always accompanied imposters and surrounded the production of copycats/fake stuff, both in life and in art, especially in comedy. Yet, the false pretending so masterfully to stand for the genuine has for some time already started to be more and more an object of worry and concern rather than of ridicule. Among the most worrying of its many manifestations has been the feeling that we, as human beings, are getting closer and closer, that we are having the world at our fingertips. One of the saddest illusions we so easily succumb to. For, in effect, we have been getting more and more estranged. During the last two years, when we needed to keep a distance and closeness was so much missed, sometimes I thought why we were not as indignant at and horrified by the invisible distancing taking ground between us long time before the pandemic. The centrifugal motion on so many levels has been getting frighteningly strong for a long time already: we have been kind of flying away from each other, mistaking communication for communion, having our bodies touch a lot but less and less experiencing the elevating feeling of our souls embrace. So much so that, I dare say, for many years before the pandemic we have been living in a time of a new Big Bang. Only it is a Big Bang that is taking place not somewhere in the universe but within the mankind itself; a Big Bang that is already happening within our own selves too – within the single human being, since we often start to question our innate sense of what is good or bad, and to what extent something is good or bad. It is like the increasing outside chaos is getting to creep inside us, throwing into disarray our inner moral magnet, that invisible thing that holds us as humanity. Isn’t the mass erosion of criteria a result exactly of an eroding of our innate criteria? How have theatre and criticism been affected by this dwelling of ours in sort of a mirage-universe? How have they responded to the different faces of the false? While trying to open a conversation on this topic, I’ll also try to outline the evolving response of the critics and the search for possible waysout en route back to the genuine.